Assignment of the somatic A/B compartments to chromatin domains in giant transcriptionally active lampbrush chromosomes - Alla Krasikova; Tatiana Kulikova; Juan Sebastian Rodriguez Ramos; Antonina Maslova (Epigenetics & Chromatin, 2023)
Abstract Background The three-dimensional configuration of the eukaryotic genome is an emerging area of research. Chromosome conformation capture outlined genome segregation into large scale A and B compartments corresponding mainly to transcriptionally active and repressive chromatin. It remains unknown how the compartmentalization of the genome changes in growing oocytes of animals with hypertranscriptional type of oogenesis. Such oocytes are characterized by highly elongated chromosomes, called lampbrush chromosomes, which acquire a typical chromomere-loop appearance, representing one of the classical model systems for exploring the structural and functional organization of chromatin domains. Results Here, we compared the distribution of A/B compartments in chicken somatic cells with chromatin domains in lampbrush chromosomes. We found that in lampbrush chromosomes, the extended chromatin domains, restricted by compartment boundaries in somatic cells, disintegrate into individual chromomeres. Next, we performed FISH-mapping of the genomic loci, which belong to A or B chromatin compartments as well as to A/B compartment transition regions in embryonic fibroblasts on isolated lampbrush chromosomes. We found, that in chicken lampbrush chromosomes, clusters of dense compact chromomeres bearing short lateral loops and enriched with repressive epigenetic modifications generally correspond to constitutive B compartments in somatic cells. A compartments align with lampbrush chromosome segments with smaller, less compact chromomeres, longer lateral loops, and a higher transcriptional status. Clusters of small loose chromomeres with relatively long lateral loops show no obvious correspondence with either A or B compartment identity. Some genes belonging to facultative B (sub-) compartments can be tissue-specifically transcribed during oogenesis, forming distinct lateral loops. Conclusions Here, we established a correspondence between the A/B compartments in somatic interphase nucleus and chromatin segments in giant lampbrush chromosomes from diplotene stage oocytes. The chromomere-loop structure of the genomic regions corresponding to interphase A and B compartments reveals the difference in how they are organized at the level of chromatin domains. The results obtained also suggest that gene-poor regions tend to be packed into chromomeres.